Synthesis and characterization of thermosensitive poly(organophosphazenes) with methoxy-poly(ethylene glycol) and alkylamines as side groups - Lee, BH; Lee, YM; Sohn, YS; Song, SC (WILEY-V C H VERLAG GMBH, 2002)
Thermosensitive poly(organophosphazenes) bearing methoxy-poly(ethylene glycol) (MPEG) and alkylamines as substituents have been synthesized and characterized by elemental analysis, NMR spectroscopy, GPC, and DSC. All the polymers exhibited crystallinity, which was probably induced by the MPEG side chain of the polymers. All the polymers exhibited the lower critical solution temperature (LCSTs) in the range of 28 to 94 T depending on several factors such as mole ratio of the substituents, kinds of PEG and alkylamines. The higher content of MPEG and shorter chain length of alkylamines of the polymers afforded the higher LCST. The LCSTs of the polymers exhibited almost concentration-independent behavior in the range of 3-30 wt % of the polymers in aqueous solutions. The polymers showed the higher LCSTs in the acidic solutions than in the neutral and basic solutions. The ionic strength of the polymer solution affected the LCST, which decreased with increased NaCl concentration. The polymer bearing almost equimolar substitutuents with the -N-P-N- unit has shown the LCST more sensitive to NaCl and pH than that with the -N-P-O- unit. The polymers were found to degrade in acidic solution but be very stable in alkali solution as well as in the buffer solution of pH 7.4.
Keywords: AMINO-ACID ESTERS; TEMPERATURE; POLYMERS; POLYPHOSPHAZENES; SOLUBILITY; SYSTEM; ETHER